Central aortic pressure improves prediction of cardiovascular events compared to peripheral blood pressure in short-term follow-up of a hypertensive cohort. (2nd January 2020) - Zuo, Junli; Chang, Guili; Tan, Isabella; Butlin, Mark; Chu, Shao-li; Avolio, Alberto
ABSTRACT: Objective : The aim of this study was to assess indices of a comprehensive panel of central aortic pressure and arterial stiffness for prediction of cardiovascular events in a hypertensive cohort. Methods : Noninvasive measurements of central aortic blood pressure, brachial pressure, wave reflection augmentation index, pressure amplification, pulse wave velocity (PWV) and carotid intima-media thickness (IMT) were obtained in 675 hypertensive patients (age 61 ± 9 years, 425 males) for a mean follow-up period 25 ± 4 months. The primary endpoints were defined as cardiovascular disease (CVD) events or death from CVD. Results : After adjusting for confounding factors, central systolic (cSBP) and pulse pressure (cPP) showed higher hazard ratios (HR/10 mmHg) for cardiovascular events (CV) compared to peripheral pressure indices (pSBP, pPP) at age >60 years (cSBP: HR = 1.18, pSBP: HR = 1.17, p = 0.034; cPP: HR = 1.28, pPP: HR = 1.2, p = 0.019). Each SD increase in IMT and in central augmented pressure (cAP) entailed a 1.4 times higher risk of increased total events in elderly patients (age >60 years). For males, each SD increase in cAP was associated with 1.36 times higher risk of increased total events. For females, each SD increase in cAIx and cAP was associated with 0.4 and 0.5 times lower risk of increased total and major CV, respectively. This sex difference is most likely due to lack of age-related increase of cAIx in females after age >60 years compared to males. Conclusions : Central pressure improved prediction of CVD compared to peripheral pressure during a relatively short-term follow up of approximately 2 years at age >60 years.